The receptions and social media actions on Malaysia political online documentary among Generation Z - Mohd. Nor Shahizan Ali; Zairul Anuar Mat Dawam; Nur Azlan Zainuddin; Neesa Ameera Mohamed Salim (Institut Penyiaran Dan Penerangan Tun Abdul Razak, 2022)
The rise of social media today is drastically changing the way information are being shared among the society. Social media has allowed the digital users to disseminate various issues including political issues. The aim of this study is to define the key receptions and social media actions among the Generation Z towards Malaysian political online documentary, ‘Kisah Tauke Mancis dan Minyak Tumpah’, an award winning documentary in Freedom Film Fest (FFF) 2011. A qualitative approach was carried out through focus group discussions with 21 informants in Malaysia to collectively analyse the key receptions and social media actions. The focus group discussion was based on two key factors i) internal (Narrative, Visual Images and Themes) and ii) external (The Internet, and Media Ethics). Findings revealed that the internal factors are significantly relevant in defining the receptions of the users in comparison to external factors which influenced the social media actions.